Capacitors
By embedding barium titanate grains in the dielectric layer of the capacitor and using the core-shell structure distribution of rare earth elements and silicon, the problem of low dielectric constant in existing capacitors is solved, and the improvement of high dielectric constant and high temperature insulation resistance is achieved.
Patent Information
- Application Number
- CN202080088037.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-12-23
- Filing Date
- 2020-12-11
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2040-12-11
AI Technical Summary
Existing capacitors have out-of-phase and grain boundary phases with relatively low dielectric constants in the dielectric layer, resulting in insufficient electrostatic capacitance and high-temperature insulation resistance.
By embedding grains of barium titanate in the dielectric layer, the core-shell structure distribution of rare earth elements and silicon is used to increase the relative dielectric constant of the dielectric layer and reduce the volume ratio of the out-of-phase and grain boundary phases.
The high dielectric constant of the dielectric layer is achieved, and the electrostatic capacitance of the capacitor and the insulation resistance at high temperatures are improved.
Smart Images

Figure CN114846569B_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to capacitors. Background Art
[0002] An example of the prior art is described in Patent Document 1.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2011-132056 Summary of the invention
[0006] The capacitor disclosed in the present invention comprises a capacitor body in which a dielectric layer and an internal electrode layer are alternately stacked in multiple layers; the dielectric layer comprises crystal grains with barium titanate as a main component, a rare earth element and silicon; the crystal grains comprise a first crystal grain and a second crystal grain; when a surface portion of the crystal grain is used as a shell portion and an inner portion surrounded by the shell portion is used as a core portion, the first crystal grain has a distribution in which the concentration of the rare earth element is higher in the shell portion than in the core portion; the second crystal grain has a distribution in which the concentration ratio of the silicon in the core portion and the shell portion is smaller than the concentration ratio of the rare earth element in the core portion and the shell portion of the first crystal grain. BRIEF DESCRIPTION OF THE DRAWINGS
[0007] The objects, features and advantages of the present disclosure will become more apparent from the following detailed description and accompanying drawings.
[0008] Figure 1 It is a perspective view of the appearance of a capacitor shown as an example of an embodiment.
[0009] Figure 2 yes Figure 1 Sectional view along line ii-ii.
[0010] Figure 3 yes Figure 2 An enlarged view of section P1.
[0011] Figure 4 yes Figure 3 An enlarged view of part P2.
[0012] Figure 5 It is a schematic cross-sectional view partially showing a dielectric layer constituting a capacitor according to another embodiment. DETAILED DESCRIPTION
[0013] The capacitor (hereinafter referred to as capacitor) which is the basic structure of the capacitor of the present disclosure has been developed with the dielectric layer and the internal electrode layer being made thinner for the purpose of miniaturization and higher capacitance.
[0014] In the past, dielectric materials with barium titanate as the main component were used in the dielectric layers constituting the capacitors. In this case, in addition to barium titanate, the dielectric layer also contains components for adjusting the temperature characteristics of the electrostatic capacitance or components for improving the reduction resistance of the dielectric layer. In the capacitor whose structure is the basis of the capacitor disclosed in the present invention, components other than barium titanate are contained in the dielectric layer as heterophases and grain boundary phases. Therefore, the amount of these heterophases and grain boundary phases present in the dielectric layer lowers the relative dielectric constant or electrostatic capacitance. Therefore, the applicant tried to see whether it was possible to achieve a high dielectric constant of the dielectric layer by embedding components of heterophases and grain boundary phases with low relative dielectric constants into the grains of barium titanate.
[0015] The following is based on Figure 1 to Figure 5 The capacitor of the embodiment is described. It should be noted that the present disclosure is not limited to the specific embodiments described below. The present disclosure may include various forms as long as it conforms to the spirit or scope of the general disclosure concept defined by the appended claims.
[0016] like Figure 1 As shown in FIG. 1 , the capacitor shown as an example of an embodiment includes a capacitor body 1 and external electrodes 3 provided on the end surfaces thereof. Figure 2 As shown in FIG. 1 , the capacitor body 1 includes a dielectric layer 5 and an internal electrode layer 7. The dielectric layer 5 and the internal electrode layer 7 are alternately stacked in a plurality of layers. Figure 2 In the figure, the number of dielectric layers 5 and internal electrode layers 7 is simplified to a few layers, but the number of dielectric layers 5 and internal electrode layers 7 is actually several hundred layers. The external electrode 3 is electrically connected to the internal electrode layer 7. Figure 3 As shown, the dielectric layer 5 is a sintered body of crystal grains 9. The main component of the crystal grains 9 is barium titanate. The dielectric layer 5 is a sintered body formed mainly of crystal grains 9 with barium titanate as the main component. The main component refers to the case where the mass ratio occupied in the dielectric layer 5 is 70% by mass or more. The main body refers to the case where the volume ratio occupied in the dielectric layer 5 is 70% by mass or more. In the following, the structure with crystal grains 9 with barium titanate as the main component as the main body is sometimes expressed as barium titanate grains 9. Other components are usually present as different grains from the barium titanate grains 9, and as heterophases 11 or grain boundary phases 13 between the barium titanate grains 9. Here, heterophase refers to a portion confirmed to be crystalline by analysis such as X-ray diffraction. The grain boundary phase refers to a portion that exists in a manner surrounding the crystal grains 9. In this case, the grain boundary phase refers to a portion formed at the dihedral grain boundary and the triple point grain boundary. In many cases, the grain boundary phase contains an amorphous phase.
[0017] The dielectric layer 5 constituting the capacitor of the embodiment includes grains 9 of barium titanate, and at least rare earth elements (RE) and silicon (Si). Rare earth elements (RE) are elements belonging to the lanthanide series in the periodic table. Here, as a particularly preferred rare earth element (RE), in addition to dysprosium (Dy), gadolinium (Gd), terbium (Tb), holmium (Ho) and erbium (Er), yttrium (Y) is also exemplified. Rare earth elements (RE) are used as a component for improving the reduction resistance and insulation of the dielectric layer 5. Silicon is mainly used as a sintering aid for the grains 9. Among these components, the grains 9 of barium titanate are mainly responsible for the high dielectric constant of the dielectric layer 5. The phases formed by components other than barium titanate have relative dielectric constants that are mostly two to three degrees lower than those of the grains 9 of barium titanate. Here, the dielectric properties of the dielectric layer 5 formed by the sintered body of the grains 9 are described. The relative dielectric constant of the dielectric layer 5 constituting the capacitor is determined by the volume mixing ratio of the plurality of crystal grains 9, the heterogeneous phase 11, and the grain boundary phase 13, which respectively exhibit the inherent relative dielectric constant. Here, the relative dielectric constant determined by the volume mixing ratio is taken as the composite dielectric constant. In this case, the higher the volume ratio of the crystal grains 9 of barium titanate, the higher the composite dielectric constant. In other words, when the volume ratio of the heterogeneous phase 11 and the grain boundary phase 13 of the crystal grains 9 having a relative dielectric constant lower than that of barium titanate increases, the overall relative dielectric constant (composite dielectric constant) of the dielectric layer 5 decreases.
[0018] The crystal grains 9 constituting the dielectric layer 5 include a plurality of crystal grains forming a core-shell structure. The core-shell structure of the crystal grains 9 is determined by the concentration distribution of the rare earth element (RE) contained in the crystal grains 9. Here, the crystal grains 9 are first divided into crystal grains 9 having a core-shell structure and crystal grains 9 not having a core-shell structure. If other expressions are used, the dielectric layer 5 includes a first crystal grain 9A and a second crystal grain 9B. Here, the first crystal grain 9A is a crystal grain 9 having a core-shell structure. The first crystal grain 9A has a distribution in which the concentration of the rare earth element (RE) is higher in the shell portion 9a than in the core portion 9b. From the viewpoint of the concentration distribution of the rare earth element (RE), the first crystal grain 9A is a crystal grain 9 having a core-shell structure.
[0019] The second crystal grain 9B is a crystal grain 9 in which silicon is distributed at a high concentration not only in the shell portion 9a which is the surface portion of the crystal grain 9, but also in the core portion 9b which is the inside. In other words, the second crystal grain 9B has a distribution in which the concentration ratio of silicon in the shell portion 9a and the core portion 9b is smaller than the concentration ratio of the rare earth element (RE) in the shell portion 9a and the core portion 9B of the first crystal grain 9A.
[0020] In the dielectric layer 5, most of the silicon contained therein is solid-dissolved in the grains 9 of barium titanate. Therefore, in the dielectric layer 5, the volume ratio of the heterogeneous phase 11 or the grain boundary phase 13 caused by silicon is reduced compared with the conventional dielectric layer 5. As a result, the composite dielectric constant of the dielectric layer 5 becomes higher, and the electrostatic capacitance of the capacitor can be increased. In addition, in the capacitor of the embodiment, the insulation resistance at high temperature can be increased. In this case, the high temperature is, for example, 100°C or more. Specifically, the insulation resistance at 125°C.
[0021] In the first crystal grain 9A, when the concentration of the rare earth element (RE) contained in the shell portion 9a is set to Csr and the concentration of the rare earth element (RE) contained in the core portion 9b is set to Ccr, the ratio of Csr / Ccr is greater than or equal to 2 and less than or equal to 20. In the second crystal grain 9B, when the concentration of silicon contained in the shell portion 9a is set to Css and the concentration of silicon contained in the core portion 9b is set to Ccs, the ratio of Css / Ccs is greater than or equal to 1 and less than or equal to 1.5. In this case, in the dielectric layer 5 constituting the capacitor of the embodiment, the second crystal grain 9B can be included in the dielectric layer 5 at a number ratio of greater than 80%, particularly greater than 90%.
[0022] Figure 5 It is a schematic cross-sectional view partially showing a dielectric layer constituting a capacitor according to another embodiment. Figure 5 The dielectric layer 5 shown has crystal grains 9 containing silicon and rare earth elements. Figure 5 The dielectric layer 5 shown includes crystal grains (third crystal grains 9C) that do not have a core-shell structure when observing the concentration distribution of silicon but have a core-shell structure when observing the concentration distribution of the rare earth element (RE).
[0023] That is, when the concentration distribution of the rare earth element (RE) is evaluated for the second crystal grain 9B, the third crystal grain 9C has a state in which the concentration of the rare earth element (RE) is higher in the shell portion 9a than in the core portion 9b. In this case, the second crystal grain 9B becomes a crystal grain 9 having only the aforementioned concentration distribution of silicon, and the rare earth element (RE) is not a core-shell structure. In this case, the third crystal grain 9C can be included in the dielectric layer 5 at a number ratio of 80% or more.
[0024] In addition, in the capacitor of the embodiment, the capacitor body 1 may have a dielectric layer 5 including at least one of the second crystal grain 9B and the third crystal grain 9C in all layers. Here, all layers refer to all dielectric layers 5 that contribute to the expression of electrostatic capacitance in the capacitor. In other words, all layers refer to the portion from which the cover layer is removed from the capacitor body 1. In this case, any layer of all dielectric layers 5 that contribute to the expression of electrostatic capacitance in the capacitor body 1 may include the first crystal grain 9A.
[0025] Next, the method of observing and evaluating the above-mentioned structure in the dielectric layer 5 is described. In the capacitor body 1, the state of the dielectric layer 5 and the internal electrode layer 7 stacked or the filling degree of the grains 9 are evaluated by observation and photography using a digital microscope or an electron microscope. The identification of the compound constituting the grains 9 of the dielectric layer 5 uses X-ray diffraction and electron beam diffraction based on a transmission electron microscope. In the determination of the elements in the grains 9 constituting the dielectric layer 5, the characteristic X-rays are measured using an analyzer (energy dispersion type) attached to the transmission electron microscope. The concentrations of the elements contained in the shell 9a and the core 9b of the grains 9 are also measured using an analyzer attached to the transmission electron microscope. In this case, the intensity (count) of the characteristic X-rays generated by the rare earth elements and silicon contained in the shell 9a and the core 9b are respectively obtained as Csr, Ccr, Css, and Ccs. Next, the ratio Csr / Ccr of the intensity Csr of the characteristic X-ray of the rare earth element in the shell 9a to the intensity Ccr of the characteristic X-ray of the rare earth element in the core 9b is calculated. The ratio Css / Ccs of the intensity Css of the characteristic X-ray of silicon in the shell 9a to the intensity Ccs of the characteristic X-ray of silicon in the core 9b is calculated. The first crystal grain 9A, the second crystal grain 9B, and the third crystal grain 9C are determined based on the intensities Csr / Ccr and Css / Ccs of the elements thus obtained, and their numbers are respectively obtained. In this case, the crystal grains 9 to be analyzed are those with a maximum diameter of 0.1 μm or more. When the maximum diameter of the crystal grain 9 is less than 0.1 μm, it is difficult to know the state of the concentration distribution of the rare earth element contained in the crystal grain 9. Therefore, it becomes difficult to evaluate whether the crystal grain 9 is a core-shell structure. In the crystal grain 9, the boundary between the shell portion 9a and the core portion 9b is, for example, a region where the intensity of the characteristic X-ray in the shell portion 9a changes significantly relative to the intensity of the characteristic X-ray in the core portion 9b when the concentration distribution of the rare earth element (RE) is measured. The crystal structure of such a boundary changes from tetragonal to quasi-cubic. This analysis is performed using a specific cross section of the dielectric layer 5. The cross section is targeted at the region connected to the crystal grains 9. In this case, the number of crystal grains 9 is more than 10 and less than 100. The analysis is performed on 1 to 10 layers in the central portion of the stacking direction of the dielectric layer 5 constituting the capacitor body 1, but when necessary, all layers of the dielectric layer 5 constituting the capacitor body 1 are sometimes analyzed. In this case, the position of the analysis can also be the central portion in the width direction of the dielectric layer 5.
[0026] In addition to the above-mentioned components, the dielectric layer 5 constituting the capacitor of the embodiment may also contain magnesium (Mg) and manganese (Mn). Magnesium (Mg) is used to adjust the temperature characteristics of the electrostatic capacitance of the capacitor. Manganese (Mn) is used to improve the reduction resistance of the dielectric layer 5. In addition, a sintering aid such as glass powder containing other elements in silicon oxide may be contained in the dielectric layer 5 as needed.
[0027] Next, the manufacturing method of the capacitor of the embodiment is described. In the capacitor of the embodiment, on the ceramic green sheet for forming the dielectric layer 5, in addition to using the pre-fired powder shown below, it can be made by the conventional manufacturing method of the capacitor. In this case, the pre-fired powder is prepared by mixing the barium titanate powder and the silicon component (powder containing silicon oxide) and pre-firing. If such a pre-fired powder is used as the raw material powder, silicon is easily dissolved in the interior of the barium titanate powder. In addition, when the ratio of the number of grains 9 in which silicon is dissolved in the interior of the grains 9 changes, the amount of powder containing silicon oxide added relative to the barium titanate powder is changed.
[0028] Example
[0029] The following is a detailed description of capacitor manufacturing and characteristic evaluation. First, barium titanate (BaTiO3) powder, magnesium carbonate (Mg2CO3) powder, dysprosium oxide (Dy2O3) powder, manganese carbonate (MnCO3) powder, and a sintering aid powder (SiO2=55, BaO=20, CaO=15, Li2O3=10 (mol%)) are prepared as raw material powders for preparing dielectric powders. In this case, barium titanate powder with an average particle size of 0.25 μm is used. The composition of the dielectric powder is as follows: 0.8 mol of magnesium oxide (MgO) powder, 0.8 mol of dysprosium oxide (Dy2O3) powder, and 0.3 mol of manganese carbonate (MnCO3) powder in terms of MnO are added to 100 mol of barium titanate powder, and 1 part by mass of powder (SiO2-BaO-CaO-based glass powder) as a sintering aid is added to 100 parts by mass of the barium titanate powder. Here, the powder as a sintering aid is added in an amount of a predetermined ratio (0.3 to 0.5) of the original amount of the glass component added to the barium titanate powder, and pre-fired at 800°C for 2 hours in the atmosphere to prepare a pre-fired powder.
[0030] Then, the remaining additives are added to the calcined powder, and an organic vehicle is mixed therein to prepare a slurry. The remaining additives are magnesium oxide (MgO) powder, dysprosium oxide (Dy2O3) powder, manganese carbonate (MnCO3) powder, and powder as a sintering aid.
[0031] Next, the prepared slurry was used to prepare ceramic green sheets with an average thickness of 5 μm by a doctor blade method. A butyral resin was used as the resin contained in the organic vehicle. The amount of butyral resin added was 10 parts by mass relative to 100 parts by mass of the dielectric powder. A solvent was a 1:1 mixture of ethanol and toluene. Ceramic green sheets prepared by a method without using pre-fired powder were also prepared to the same thickness. A conductor paste containing nickel powder was used as a conductor paste for forming an internal electrode pattern.
[0032] Next, a conductor paste is printed on the prepared ceramic green sheet to prepare a pattern sheet. Here, the pattern sheet prepared from the ceramic green sheet prepared using the pre-fired powder is referred to as the first sheet. The pattern sheet prepared from the ceramic green sheet prepared by a method not using the pre-fired powder is referred to as the second sheet.
[0033] Then, the first sheet and the second sheet are combined and stacked 10 layers to produce a core laminate. Next, ceramic green sheets are stacked on the upper surface and the lower surface of the core laminate as cover layers to produce a base laminate. The cover layer uses a ceramic green sheet produced by a method that does not use pre-fired powder. Then, the base laminate is cut to produce a formed body of the capacitor body.
[0034] Next, the formed body of the capacitor body is fired to produce the capacitor body. In hydrogen-nitrogen, formal firing is carried out under the conditions of a heating rate of 900°C / h and a maximum temperature set to 1190°C. This firing uses a firing furnace with resistance heating. Next, the produced capacitor body is reoxidized. The conditions for the reoxidation treatment are: in a nitrogen atmosphere, the maximum temperature is set to 1000°C and the holding time is 5 hours. The size of the capacitor body is 1mm×0.5mm×0.5mm. The average thickness of the dielectric layer is 3μm. The average thickness of the internal electrode layer is 1μm. The number of layers is 10. The design value of the electrostatic capacitance of the produced capacitor is set to 10nF.
[0035] Next, after the capacitor body is barrel-polished, external electrode paste is applied to both ends of the capacitor body and sintered at 800°C to form external electrodes. The external electrode paste uses a material to which Cu powder and glass are added. Then, Ni plating and Sn plating are sequentially formed on the surface of the external electrode using an electrolytic barrel machine to obtain a capacitor.
[0036] Next, the capacitors were evaluated as follows. First, several of the capacitors were selected and crushed using a mortar to prepare samples for X-ray diffraction. Next, the samples were subjected to X-ray diffraction to determine the main components constituting the dielectric layer.
[0037] Next, the crystal grains constituting the dielectric layer were analyzed. The capacitor sample was processed as follows for this analysis. First, the cross section of the capacitor was ground to produce Figure 2 The sample with the exposed cross section is then subjected to FIB (focused ion beam) processing to prepare a sample for observation with a transmission electron microscope.
[0038] Next, the obtained samples were analyzed and evaluated using a transmission electron microscope equipped with an analyzer. First, the following samples were selected from the photographs obtained by observation using a transmission electron microscope: Figure 3 The cross section shown includes a layer of dielectric layer. The area per unit area is the W cross section of a layer of dielectric layer. The W cross section refers to a cross section in a direction parallel to the end face of the capacitor body where the external electrode is formed in the capacitor. The selected dielectric layer is a layer in the center of the stacking direction in the cross section of the capacitor body. In addition, the center part in the width direction of the selected dielectric layer is used as the analysis site. The grains present in the area of 3μm×3μm are analyzed. This is carried out in three places.
[0039] Next, the components contained in the grains existing in the selected dielectric layer were identified. The analysis results showed that the parent phase was mainly barium titanate. In the capacitors produced, no matter which sample was produced using the pre-sintered powder, the dielectric layer contained the first grain and the second grain. In addition, the dielectric layer of the capacitor produced also contained grains identified as the third grain. When the concentration distribution of the rare earth element (RE) was evaluated for a specific grain, it had a core-shell structure. The ratio Csr / Ccr of the concentration Csr of the rare earth element (RE) in the shell of the grain identified as the first grain to the concentration Ccr of the rare earth element (RE) in the core was in the range of 7 to 8 in any grain. The concentration distribution of silicon in the same grain is a state in which silicon is contained in the interior of the grain at a high concentration. The ratio Css / Ccs of the concentration Css of silicon in the shell of the grain identified as the second grain to the concentration Ccs of silicon in the core was 1.5 in any grain.
[0040] Next, regarding the dielectric properties, the electrostatic capacitance was measured without applying a DC voltage. The conditions without applying a DC voltage were an AC voltage of 1.0 V and a frequency of 1 kHz. The number of samples was set to 30 and the average value was calculated. Figure 1Indicates the electrostatic capacitance of the measured sample. The insulation resistance at high temperature is also measured. The temperature is set to 125°C. The insulation resistance at high temperature is set to the value when a DC voltage (100V) is applied to the prepared sample (capacitor) for 1 minute in a constant temperature bath. The number of samples is set to 20 and the average value is calculated. A sample in which a ceramic green sheet made by a method not using pre-fired powder is applied to all layers is prepared and the same evaluation is performed. The grains constituting the dielectric layer of the sample in which a ceramic green sheet made by a method not using pre-fired powder is applied to all layers have a core-shell structure from the perspective of the concentration distribution of rare earth elements (RE), but no grains in which silicon is dissolved in the interior of the grains are found. At this time, grains with a signal level around the measurement error are removed.
[0041] [Table 1]
[0042]
[0043]
[0044] From the results in Table 1, it can be seen that the samples containing the second crystal grains in the dielectric layer (samples No. 2 to 4) have higher electrostatic capacitance than the sample without the second crystal grains in the dielectric layer (sample No. 1). In addition, the insulation resistance at high temperature is also high. From the X-ray diffraction and transmission electron microscope observation results of the dielectric layer of each sample, it can be confirmed that the proportion of heterophase and grain boundary phase in samples No. 2 to 4 is smaller than that in sample No. 1. Among the samples containing the second crystal grains in the dielectric layer (samples No. 2 to 4), the samples in which the number ratio of the second crystal grains contained in the dielectric layer is 80% (samples No. 3 and 4) have higher electrostatic capacitance than the sample in which the number ratio of the second crystal grains contained in the dielectric layer is 50% (sample No. 2), and the insulation resistance at high temperature is also high. Moreover, the sample (sample No. 4) in which the first sheet (ceramic green sheet made of pre-fired powder) is applied to all layers of the capacitor body has higher electrostatic capacitance and insulation resistance at high temperature than the sample (sample No. 3) in which the number of layers of the first sheet is set to half the number of layers.
[0045] The present disclosure may be implemented in the following ways.
[0046] The capacitor disclosed in the present invention comprises a capacitor body in which a dielectric layer and an internal electrode layer are alternately stacked in multiple layers; the dielectric layer comprises crystal grains with barium titanate as a main component, a rare earth element and silicon; the crystal grains comprise a first crystal grain and a second crystal grain; when a surface portion of the crystal grain is used as a shell portion and an inner portion surrounded by the shell portion is used as a core portion, the first crystal grain has a distribution in which the concentration of the rare earth element is higher in the shell portion than in the core portion; the second crystal grain has a distribution in which the concentration ratio of the silicon in the core portion and the shell portion is smaller than the concentration ratio of the rare earth element in the core portion and the shell portion of the first crystal grain.
[0047] The embodiments of the present disclosure are described in detail above. In addition, the present disclosure is not limited to the above embodiments, and various changes and improvements can be made without departing from the spirit of the present disclosure. It goes without saying that all or part of the above embodiments can be combined within an appropriate and non-contradictory range.
[0048] Explanation of symbols
[0049] 1. Capacitor body;
[0050] 3. External electrodes;
[0051] 5. Dielectric layer;
[0052] 7. Internal electrode layer;
[0053] 9. Grain;
[0054] 9A, first grain;
[0055] 9B, second grain;
[0056] 9a, shell;
[0057] 9b, core;
[0058] 11. Different phases;
[0059] 13. Grain boundary phase.
Claims
1. A capacitor having a capacitor body in which a dielectric layer and an internal electrode layer are alternately stacked in multiple layers; The dielectric layer includes grains with barium titanate as a main component, rare earth elements and silicon; The crystal grains include a first crystal grain and a second crystal grain; When the surface portions of the first crystal grain and the second crystal grain are respectively regarded as shell portions, and the inner portions surrounded by the shell portions are regarded as core portions, The first crystal grain has a distribution in which the concentration of the rare earth element is higher in the shell portion of the first crystal grain than in the core portion of the first crystal grain. Silicon is solid-dissolved in the second crystal grains. The second crystal grain has a distribution in which a concentration ratio of silicon in a core portion of the second crystal grain and a shell portion of the second crystal grain is smaller than a concentration ratio of a rare earth element in a core portion of the first crystal grain and a shell portion of the first crystal grain; In the second crystal grain, a ratio of a concentration of silicon contained in a shell portion of the second crystal grain to a concentration of silicon contained in a core portion of the second crystal grain is greater than or equal to 1 and less than or equal to 1.5; The dielectric layer includes the second crystal grains at a number ratio of 80% or more. 2 . The capacitor according to claim 1 , wherein the second crystal grains contain a rare earth element, and a concentration of the rare earth element is higher in a shell portion of the second crystal grain than in a core portion of the second crystal grain. 3 . The capacitor according to claim 1 , wherein the capacitor body has dielectric layers including the second crystal grains in all layers.
Citation Information
Patent Citations
Laminated ceramic capacitor
JP2011132056A
Dielectric ceramic and laminated capacitor
CN102040377A
Condenser
WO2013089269A1